Phenomenon of the “dawn attacks operation” as a money politics practices in Indonesian election - Djuyandi, Yusa; Mahmuda, Diana (Department of Government Studies Universitas Muhammadiyah Makassar, 2024)
The practice of handing out money before voting or dawn raids is still the choice of some legislative candidates to gain votes from citizens. Dawn attacks as a practice of money politics are an act of malpractice that can damage the democratic essence of holding general elections, because dawn attacks use money as a reciprocal tool to buy votes. This research uses qualitative methods, data is obtained from various literature, such as media, books, journals and reports related to the phenomenon of dawn attacks in the implementation of post-reform elections. The data obtained was then validated using source triangulation techniques. This research sees that several political actors who are running in the election are still carrying out dawn attacks as a political step to gain victory, however dawn attacks which are a form of money politics endanger democratic values in Indonesia, because they involve vote buying. With the dawn attacks activity, voters followed the political games of elites who only cared about getting votes without put on their capacity and capability. Once the elite who use dawn attacks are elected, then they are will be not paying attention to the public interest, corruption will continue to occur and the policies made will not be in favor of the public interest.